Study on the feasibility of recycled polyethylene terephthalate in 3D printing - Ong, Su Ting (Nanyang Technological University, 2021)
Plastics are polymers that are widely used today in various applications such as packaging, construction and consumer goods owing to their plasticity, enabling them to be extruded, moulded or pressed in different shapes and sizes needed. Most plastics are not biodegradable and takes decades to centuries for degradation. Unfortunately, plastics are unable to degrade fully, they photo-degrade to produce microplastics or even nanoplastics which can be ingested unknowingly by humans and animals. Furthermore, harmful chemicals leached from plastic waste can cause land and water pollution. Plastic waste has been on the rise in Singapore due to increasing utilisation over the years. Although there has been measures to step up plastic recycling efforts, the recycling rate is still strikingly low at 4% according to the National Environment Agency. One of the plastics that has higher disposal rate is polyethylene terephthalate (PET). The use of recycled plastics has been finding its way into several industries such as 3D printing. Various start-up companies around the globe have conceived methods to produce plastic filament for usage in 3D printing. The recycled plastics can be used to support such filament production that can be used in the 3D printing of devices or usable daily products. An experiment utilising recycled PET (rPET) in extrusion-based technology (fused filament fabrication) is reported here. This paper focuses on the results and discussion of the feasibility of recycled PET in extrusion-based technology by comparing to the virgin variation of PET which is polyethylene terephthalate glycol (PETG) that has better printability. Although the tensile test gave no conclusion on which raster orientation produces better mechanical properties, rPET has an overall higher strength as compared to PETG. Thermal characterization using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) have shown rPET to possess better thermal stability than PETG. However, rPET has lower viscosity than PETG which can be attributed to the thermal processes that caused chain scissons during recycling. rPET has lower zero shear viscosity, yield stress and higher critical shear rate than PETG. From the results obtained, it can be concluded that the rPET is feasible in extrusion-based technology with the higher strength and thermal stability although the viscosity has to be enhanced in order for improved printability.